Success factors in Singapore SMES’ internationalization. - Maria, Anna. (2008)
This study begins by presenting findings of past studies relating to the topic. Next, empirical findings and case studies are presented and analyzed. The success factors of internationalization that are pertinent to local SMEs are then identified and presented in a model.